2012
DOI: 10.1590/s0100-40422012000200018
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative validated method using liquid chromatography and chemometric analysis for evaluation of raw material oF Maytenus ilicifolia (Schrad.) Planch., Celastraceae

Abstract: Recebido em 28/3/11; aceito em 2/7/11; publicado na web em 19/8/11The hydroalcoholic extracts prepared from standard leaves of Maytenus ilicifolia and commercial samples of espinheira-santa were evaluated qualitatively (fingerprinting) and quantitatively. In this paper, fingerprinting chromatogram coupled with Principal Component Analysis (PCA) is described for the metabolomic analysis of standard and commercial espinheira-santa samples. The epicatechin standard was used as an external standard for the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…The chromatographic data pretreatment has included alignment using correlation optimized warping (COW) [31] (available at www.models.life.ku.dk/dtw_cow), normalization and mean center. Next, the unsupervised classification by principal component analysis (PCA) was applied for assessing the similarities and differences between these chromatographic profiles, because it reduces the dimensionality of original data matrix and permits the visualization of clusters within large sets of samples [23,27,32,33]. Then, the result of the initial PCA was confirmed by partial least squares discriminant analysis (PLS-DA) that is a supervised chemometric method, which builds a regression model for maximum separation between predefined classes [34].…”
Section: Discussionmentioning
confidence: 99%
“…The chromatographic data pretreatment has included alignment using correlation optimized warping (COW) [31] (available at www.models.life.ku.dk/dtw_cow), normalization and mean center. Next, the unsupervised classification by principal component analysis (PCA) was applied for assessing the similarities and differences between these chromatographic profiles, because it reduces the dimensionality of original data matrix and permits the visualization of clusters within large sets of samples [23,27,32,33]. Then, the result of the initial PCA was confirmed by partial least squares discriminant analysis (PLS-DA) that is a supervised chemometric method, which builds a regression model for maximum separation between predefined classes [34].…”
Section: Discussionmentioning
confidence: 99%
“…The other tannins of the group showed no changes in response to treatments, this condition may be another effect of the plasticity of the species previously discussed. When analyzing the presence of the compound epicatechin in 12 samples of Maytenus ilicifolia harvested in different regions of the state of Paraná, Beltrame et al (2012) found a wide variation in the content of the compound, from 250 µg mL -1 to traits identified in some samples being evaluated. These observed variations may be originated from the genetic variation of the sampled plants.…”
Section: (Preliminary)mentioning
confidence: 99%
“…Métodos de avaliação por cromatografi a líquida são um exemplo efi caz de identifi cação e quantifi cação de epicatequina em extratos brutos de M. ilicifolia que pode ser usado como controle de qualidade de fi toterápicos por laboratórios farmacêuticos (BELTRAME et al, 2012).…”
Section: Methodsunclassified